Os discursos socioculturais na internet sobre a legalização da Cannabis sativa - Costa Junior, Achylles de Oliveira (Universidade do Vale do Rio dos Sinos, 2013)
This study, developed from the perception of the existence of a speech favorable at the legalization of recreational and medicinal use of Cannabis sativa in journalistic and cultural activities, produced in a new ambience semiotics that articulates with several disciplines, such as medicine, anthropology, law, industry, fashion and arts, seeks to understand how discourses prohibitionist historically are restricted to the edges of the communication systems, and how the discursive mobilizations who oppose to prohibition or criminalization of Cannabis sativa, materialized in different media platforms constitute journalistic events, what semiosis and tension of senses are triggered. We studied newspaper articles, lyrics, videos and photos with anti-prohibitionist placements and postings of users on the Growroom discussion forum about the organization of the "marijuana marches" of São Paulo, in 2011.
Keywords: Cannabis sativa; Jornalismo; Acontecimento; Cultura; Journalism; Event; Culture; ACCNPQ::Ciências Sociais Aplicadas::Comunicação